The return of values in Australian foreign policy. Issue 2 (3rd March 2020) - Reilly, Benjamin
ABSTRACT: For many years Australia ignored or downplayed the role of values in foreign policy, preferring to focus on economic issues and engagement with Asia. Recently, however, values have re-emerged as a central aspect of Australian foreign policy, both rhetorically in government White Papers and through initiatives such as the Quadrilateral Security Dialogue comprising the established democracies of Australia, India, Japan and the United States. This commentary charts the rise of values-based language in Australian and Japanese speeches and policy documents, and argues that core concepts such as shared democratic values have an important – and under-appreciated – relevance in the new era of a rising autocratic China and in the framing of the Indo-Pacific.